The electrical properties of photodiodes based on nanostructure gallium doped cadmium oxide/p-type silicon junctions - Cavas, M.; Yakuphanoğlu, Fahrettin; Karatas, S. (Indian Assoc Cultivation Science, 2017)
Gallium doped cadmium-oxide (CdO: Ga) thin films were successfully deposited by sol-gel spin coating method on p-type Si substrate. The electrical properties of the photodiode based on nanostructure Ga doped n-CdO/p-Si junctions were investigated. The current-voltage (I-V) characteristics of the structure were investigated under various light intensity and dark. It was observed that generated photocurrent of the Au/n-CdO/p-Si junctions depended on light intensity. The capacitance-voltage and conductance-voltage measurements were carried out for this diode in the frequency range between 100 and 1000 kHz at room temperature by steps of 100 kHz. The capacitance decreased with increasing frequency due to a continuous distribution of the interface states. These results suggested that the Au/n-CdO/p-Si Schottky junctions could be utilized as a photosensor. Furthermore, the voltage and frequency dependence of series resistance were calculated from the C-V and G/omega-V measurements and plotted as functions of voltage and frequency. The distribution profile of R-S-V gave a peak in the depletion region at low frequencies and disappeared with increasing frequencies.
Keywords: Schottky barriers; Heterojunction; Electrical properties; Interface states; Photoconduction